Evaluasi Pencapaian Program Pemberantasan Penyakit Demam Berdarah Dengue (DBD) di Wilayah Kerja Dinas Kesehatan Kota Bekasi Tahun 2010-2012 - Maria Magdalena; Diana Barsasella (STIKes Persada Husada Indonesia, 2015)
Dengue fever is an infection caused by the dengue virus and transmitted through mosquito Aedes Aegypti bite. This type of research is qualitative research. Research informant are Head of P2DBD Department of Health Bekasi City, Head of P2P Department of Health Bekasi City, the field officer Department of Health Bekasi City, Head of RT 02 RW 09 Kranji Village, RT 02 RW 09 Kranji Villagecommunitywho never exposed to dengue fever, Chief of RT 03 RW 09 Village Kranji, and RT 03 RW 09 Kranji Village people who never exposed to dengue fever. The dengue eradication program in the working area of Department of Health Bekasi City include: Research Epidemiology, Fogging Focus, Larva Monitoring Periodic and Mosquito eradication nest. The results showed that the results of the implementation of P2DBD program which includes PE, FF, PJB and PSN already meets the effectiveness criteriaindicators, whereasbased on program effectiveness criteria indicators set by the central government or national indicators there are several criteria that are lacking such as the implementation of PE and FF. Barriers to implementation on P2DBD program i.e. delays from hospitals and communities in reporting cases of dengue fever, difficulty obtaining fuel (diesel), the lack of tools or ULV fogging, and public awareness to anticipate the spread of dengue is still missing. In summary the impact of the dengue disease eradication programs in Bekasi have not contributed on decreasing dengue cases annually.